Recolonization of experimental gaps by the mussels Brachidontes darwinianus and B. solisianus in a subtropical rocky shore - Tanaka,Marcel Okamoto (2005)
In this study, the recolonization speed of the mussels Brachidontes darwinianus and B. solisianus was compared to evaluate their responses to gaps opened by disturbances in the rocky shore. B. darwinianus was much faster than B. solisianus, rapidly closing gaps in the mussel bed. When they co-occurred, distribution patterns of these species were related not only with distinct physiological tolerances but also with responses to disturbance. B. darwinianus was more tolerant to low salinities, dominated estuarine zones generally occuring lower in the midlittoral, and presented a faster response to opened gaps.